Screening of rice varieties for resistance to bacterial leaf blight - Banito, A.; Kadai, E.A.; Sere, Y. (2012)
Objectives: In order to find control measures against bacterial leaf blight (BLB), one of the most destructive diseases of rice, the present study aimed to evaluate rice varieties cultivated in Togo and some near isogenic lines from IRRI for resistance to BLB in screen house. Methodology and Results: The lesions after inoculation with 13 X. oryzae pv. oryzae strains from Togo were evaluated on 21 rice varieties and near isogenic lines under screen house. The results revealed differential reactions of these genotypes in disease expression. AMMI analysis identified three groups of genotypes: resistant group made up of 12 lines IRBB1, IRBB2, IRBB3, IRBB4, IRBB7, IRBB8, IRBB10, IRBB11, IRBB13, IRBB14, IRBB21 and IR24, medium resistant group made up of three cultivars grown in Togo, NERICA4, NERICA8 and NERICA14, and one cultivar from AfricaRice, Giganté, and susceptible group including five genotypes TGR203 and IR841 from ITRA, NERICA19 and TOG5681 from AfricaRice, and the line IRBB5. Conclusions and application of findings: The results provided useful information indicating that none of rice varieties grown in Togo was resistant to bacterial leaf blight, thus revealed a potential risk of epidemics in the growing areas since these varieties were only medium resistant (NERICA4, NERICA8 and NERICA14) to susceptible (TGR203, IR841 and NERICA19). Besides, the present results are prerequisite for further screening under field conditions across ecozones of Togo (forest zone, forest savanna transition zone, wet savanna zone and dry savanna zone) and years to find out stable resistant varieties for durable production of rice